The Integration of Augmented Reality (AR) in Education - Marrahi-Gomez, Victor; Belda-Medina, Jose (Advances in Social Sciences Research Journal, 2023)
New teaching techniques have been adopted as a result of the emergence of innovative technological tools in the field of Augmented Reality (AR), as investigated in several articles to date (Hsu 2017; Forsythe & Raine 2019). The availability of AR applications, both vision, and location-based, allows students today to learn foreign languages in a more contextualized and immersive manner, thanks to the use of smartphones and other electronic devices. Thus, this study seeks to analyze and review the recent trends in AR implementation in education and to present the main projects aimed at teaching with AR-based projects that have been published in the latest years in WOS and Scopus.